NURSING CARE FOR MOTHERS WITH INCOMPLETE ABORTIONS: CASE STUDY - Fadliyah, Lailatul; Puspitaningtyas, Danty Indra; Sulpat, Emuliana; Ma'rifah, Umi (Universitas Airlangga, 2022)
Introduction: Incomplete abortion is bleeding in pregnancy before 20 weeks, where some of the products of conception have come out of the uterine cavity through the cervical canal left in the decidua or placenta. Methods: This research uses a case study design. Data collection from assessment to nursing evaluation was carried out in the jasmine room of Dr Soegiri Lamongan Hospital in February 2019. Participant care at the hospital for three days”data collection techniques using interviews, observation, and documentation. Data analysis uses narrative analysis based on the analysis of relevant facts and theories. Results: The assessment of the two participants was the first and second pregnancies, with gestational ages of 12 and 16 weeks, experiencing vaginal bleeding and abdominal pain. There is abdominal tenderness, a pain scale of 5, and uterine contractions on examination. The nursing diagnosis was acute pain associated with uterine contractions and fluid volume deficit related to bleeding (abortion). The evaluation was carried out for 72 hours of reduced pain. The discussion is expected that nurses provide health education about pain and incomplete abortion. Conclusions: The pain and anxiety were reduced after implementing nursing for 72 hours. The reference from this study is for nurses to provide health education related to pain in incomplete abortion.